Efecto de la fertilización orgánica mineral sobre la producción de maíz morado (Zea mayz l.) - Farfán, Hernán (2021)
The objective of the research was to evaluate the effect of organic mineral fertilization on the production of purple corn (Zea mayzL.) in the community of Rurunmarca, Caja Espíritu district, Acobambaprovince, Huancavelica Region, of November 2019 to May 2020 in which six fertilizations were evaluated: AO 75% + NPK 25%; AO 50% + NPK 50%; AO 25% + NPK 75%; AO 100% + NPK 100%; AO 100% and NPK 100% and a witness. These were distributed in a completely random block design. The variables evaluated were number, weight and yield of corn cobs, and profitability of fertilizations. The results indicate that fertilizations with high proportions of soluble nutrients significantly increase the number and weight of purple corn cobs by unit surface, consequently mineral organic fertilization if it influences the yield of purple corn cobs by unit area and the best cost-effective alternatives for growing purple corn is fertilizing with 25% organic manure + 75% NPK, as well as with balanced proportions of 50% organic manure + 50% NPK.